Desensitisasi Bersistem (CBT-SD) Terhadap Simptomatologi PTSD Mangsa Buli: Satu Kajian Kes - Mustapa Kamal, Siti Fadhlina; Syed Abdullah, Syed Mohamad; Sawai, Rezki Perdani (‘Abqari Journal, 2021)
Bullying not only has a significant influence on victims' physical and emotional well-being, but they are also reported to experience symptoms of post-traumatic stress disorder (PTSD) such as nightmares, intrusive thoughts and emotions of hopelessness and powerlessness. The symptomatology of untreated PTSD exposes victims to other psychological issues such as substance abuse, depersonalization and suicide. This case study was conducted to identify the effectiveness of Cognitive Behavioral Therapy-Systematic Desensitization (CBT-SD), a counseling intervention for reducing symptomatology of PTSD. He was diagnosed with clinically severe symptomatology of PTSD (T> 65) by using the Detailed Assessment of Posttraumatic Stress (DAPS) (Briere, 2001). The treatment planning using CBT-SD technique was constructed aimed at answering the research questions. The results indicate a decrease in the symptomatology of PTSD and other psychological issues, particularly on the scales of dissociation and suicide. Reducing PTSD symptoms has a favourable impact on the client’s cognitive, emotional and behavioural functioning, as seen by his improved personal functioning in his daily life. Hence, prevention and early rehabilitation through counseling interventions are crucial in aiding victims of bullying achieve psychological balance. The implications of this intervention are also discussed.